2021
DOI: 10.33457/ijhsrp.944100
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Covid-19 Fear in Terms of Its Defining Characteristics

Abstract: The study aims to determine the fear of coronavirus and its affecting factors. It was conducted as a cross-sectional study. Data on participants were collected using an online questionnaire spread throughout social media, e-mail, and WhatsApp groups. Socio-demographic questionnaire form, and Visual Analogue Scale (VAS) were used to collect data. Number, percentage, mean, t-test, One-Way ANOVA, and Pearson correlation analysis were used to evaluate the research data. The research was completed with 727 people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…6,17 Moreover, developing COVID-19 prevention and management policies that contain a special focus on gender and determining whether men are willing to declare the fear lesser in further studies are proposed. 18 It was discovered that the students who do not have jobs have higher levels of fear than those who do. According to Gökkaya et al, people who are unemployed have higher levels of coronaphobia and fear of COVID-19 than people who are employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,17 Moreover, developing COVID-19 prevention and management policies that contain a special focus on gender and determining whether men are willing to declare the fear lesser in further studies are proposed. 18 It was discovered that the students who do not have jobs have higher levels of fear than those who do. According to Gökkaya et al, people who are unemployed have higher levels of coronaphobia and fear of COVID-19 than people who are employed.…”
Section: Discussionmentioning
confidence: 99%
“…18.01±7.63) had a greater level of fear than those who were infected with COVID-19 (17.96±6.68); there is no significant…”
mentioning
confidence: 85%
“…Inappropriate parenting behaviors such as being overprotective, giving less autonomy, and transferring psychological distress and stress to their children may contribute to the development of posttraumatic stress symptoms in children (Cobham & McDermott, 2014). Among such problems there are emotional and behavioral changes, disruptions in diet and sleeping habits, increased levels of anxiety, depression, fear, and disrupted social interactions (Çimke, Gürkan, & Esenkaya, 2021; Orgilés et al, 2020; Ren et al, 2021). Parents who considered themselves to be more stressed indicated that their children were more anxious, nervous, sad, irritable and bored, had difficulty in concentrating and sleeping, and were more dependent on them (Orgilés et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%